On the peripheral tube description of the two-particle correlations in nuclear collisions. (13th February 2019) - Wen, Dan; Castilho, Wagner Maciel; Lin, Kai; Qian, Wei-Liang; Hama, Yogiro; Kodama, Takeshi
Abstract: In this work, we study the two-particle correlations regarding a peripheral tube model. From our perspective, the main characteristics of the observed two-particle correlations are attributed to the multiplicity fluctuations and the locally disturbed one-particle distribution associated with hydrodynamic response to the geometric fluctuations in the initial conditions (IC). We investigate the properties of the IC and collective flow concerning the proposed model. It is shown that the experimental data can be reproduced by hydrodynamical simulations using appropriately constructed IC. Besides, instead of numerical calibration, we extract the model parameters according to their respective physical interpretations and show that the obtained numerical values are indeed qualitatively in agreement with the observed data. Possible implications of the present approach are discussed.